Critical insights into the attributes of an effective board of directors as a deterrent to corporate fraud - Mohd Uzir, Abdul Azim; Mohd Saat, Nur Ashikin (Research and Scientific Innovation Society, 2023)
This paper examined the characteristics of board of directors that are effective in mitigating corporate frauds by critically reviewing findings from previous and recent studies. The board of directors’ roles are first assessed in order to investigate their statutory duties and responsibilities, which will influence their governing actions to implement and enforce monitoring and disciplining measures to prevent misconduct and malpractice. The gender diversity of board members, corporate experience, independence, and frequency of board meetings are key board authorities, reputation, and influence in controlling fraudulent conduct in organisations. The establishment of specific law enforcement authorities and laws, specifically the Anti-Corruption Commission, the Anti-Money Laundering, Anti-Terrorism Financing, and Proceeds of Unlawful Activities, the Penal Code, and the Companies Act, are critical components in ensuring that fraudulent activities are prevented.